Membaca Lancar Level 2 Siswa Kelas 2 SD - Miranda Novita Permata Sari Lubis; Chandra Chandra; Salmaini Syafitri Syam (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Fluent reading is the ability to understand symbols in the form of words by paying attention to several aspects, including the ability to recognize words, automatic reading skills, speed in transitioning from one word to another, the use of intonation and expression in oral reading, and accuracy in understanding the meaning of the words being read. Therefore, this study aims to analyze the fluent reading ability of second-grade students, focusing on the aspects of accuracy, speed, and fluency in reading, including pauses, intonation, and expression. This research adopts a case study method with a reading test technique designed to assess these three main components. The subjects of this study are five second-grade students from a primary school.